Relatıonshıp Between The Health Perceptıon and Physıcal Actıvıty of Indıvıduals - Neslihan Lök; Kerime Bademli (Selcuk University, 2018)
This research was conducted to determine the relationship between physical activity and health perception in the general adult population. This is a descriptive and correlational study intended to describe the correlation between health perception and the physical activity of adults. The sample was all voluntary 96 participation. The data were collected by the Perception of Health Scale and International Physical Activity Questionnaire. Number and percentile distributions were examined and the t-test was used. Pearson correlation Coefficient (Pearson r) was also used to test the correlation between Perception of Health Scale and International Physical Activity Questionnaire-IPAQ. The socio demographic data of the adult individual showed that their average age was 27.13±2.28, that  62.8'% were female, and that 31,2%  were male,  57,3% had completed primary school, 42.7% high school and upper . Of them, 41.7% were married, and 58.3% single.   87.5% had children. 76% live in the city, 24% live in rural areas and 63.5% perceive the economic situation as good and 36.5% as moderate. When the scores of the individuals in the physical activity questionnaire were evaluated, 23.9% were found to be inactive and 76.1% were found to be the least active. In this study it was observed that the majority of participants were physically active. That the less educated, men, singles, lower economic status and lived in the urban area   have low health perception scores.  In this study there was a strong correlation between the physical activity level and the control center on the positive side, a weak relationship between the self-awareness and the positive side in the positive direction. Physical activity was related to better self-health perception.